DISEMINASI PENGGUNAAN JAMUR TRICHODERMA SEBAGAI BIOFUNGISIDA PADA TANAMAN BAWANG DAUN (Allium fistulosum) DI KECAMATAN BATHIN VIII KABUPATEN SAROLANGUN - Putri Lisan Purnama Sari; Endang Krisnawati; Nawangwulan Widyastuti (Jurnal Inovasi Penelitian, 2020)
Wise consideration of the use of chemical pesticides in farming should be given to environmental sustainability. One of the biopestithat was developed was a biofungisida that functioned to control diseases caused by pathogenic fungi. The use of Trichoderma fungi as biofungisids can reduce the use of chemical fungicides. Howevwe, the distribution of information on Trichoderma mushrooms has not reached all major perpetrators in Bathin VIII district, som many farmers are unawaere of the Trichoderma fungu’s biological agents. The study is conducted at the inside Bathin VIII district of Sarolangun. Sample in the study of as many as 46 farmers taken usung tedium sampling techniques. Free vaeiables covering internal, exsternal factors, and innovation and interconnected variables are enabled by the use of Trichoderma mushrooms as a biofungisida. The analysis techniques used are descriptive analisis, linear regression analysis, and Kendall;s W analysis. The results of the study indicate that a farmers knowledge, attitude, and skill were moderate. Factors that influence the behavior of farmers in the cultivation og Trichoderma mushrooms are internal factors and innovation. The strategies used to improve skilla are by conducting outings and demonstrations of ways on techniques to make Trichoderma mushrooms and how to make biofungisids from the Trichoderma mushrooms for plants.